2018
DOI: 10.1097/bor.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of biochemical markers in osteoarthritis: current update

Abstract: Osteoarthritis is the most common form of joint disease. This presents the osteoarthritis research community and pharmaceutical companies developing disease-modifying osteoarthritis drugs (DMOADs) with great opportunities. There are different osteoarthritis subtypes, which complicates the traditional approaches for developing new treatments. If we can identify new markers that can distinguish different subtypes, this can greatly facilitate drug development from early discovery to late clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
1
39
0
2
Order By: Relevance
“…An improved beneficial response to therapeutic injection after arthrocentesis may result from confirmation that the drug was actually delivered into the synovial space as some OA patients have very small SF volumes . It is also plausible that the therapeutic agent may have a prolonged half‐life following arthrocentesis due to a reduced concentration of catabolic synovial fluid cytokines and proteinases since even OA patients exhibit a SF profile of elevated inflammatory mediators and catabolic proteins which could degrade an injected drug more rapidly . There may also be greater detail observed on US images from RA patients since a larger area frequently identifies enhanced detail on the size of the synovial pannus and provides a larger area available for inspection and possibly to address adequacy of therapy following biologic therapy as reviewed by Vlad et al We did not perform power Doppler examination on the knees in this study so we cannot address if inflation to 100 mmHg might influence blood flow as assessed by power doppler signal generation.…”
Section: Discussionmentioning
confidence: 99%
“…An improved beneficial response to therapeutic injection after arthrocentesis may result from confirmation that the drug was actually delivered into the synovial space as some OA patients have very small SF volumes . It is also plausible that the therapeutic agent may have a prolonged half‐life following arthrocentesis due to a reduced concentration of catabolic synovial fluid cytokines and proteinases since even OA patients exhibit a SF profile of elevated inflammatory mediators and catabolic proteins which could degrade an injected drug more rapidly . There may also be greater detail observed on US images from RA patients since a larger area frequently identifies enhanced detail on the size of the synovial pannus and provides a larger area available for inspection and possibly to address adequacy of therapy following biologic therapy as reviewed by Vlad et al We did not perform power Doppler examination on the knees in this study so we cannot address if inflation to 100 mmHg might influence blood flow as assessed by power doppler signal generation.…”
Section: Discussionmentioning
confidence: 99%
“…Since metabolic alterations of chondrocytes usually precede the structural damage of cartilage, associated biomarkers are highly relevant for early diagnosis and might also allow a prediction of rapid disease progression. Biomarkers studied in OA are mostly associated with extracellular matrix turnover of cartilage, joint inflammation, or general metabolic parameters [8,9]. Although a broad spectrum of potential systemic markers has been tested only a few of them have repeatedly shown promising results.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, 14 million people have symptomatic knee osteoarthritis (KOA) (Vina and Kwoh, 2017). Approximately 10–20% adult have OA (Bay-Jensen et al, 2018). Although OA is considered a disease primarily for the elderly, nowadays, more than half of patients with OA are under 65 years old.…”
Section: Introductionmentioning
confidence: 99%
“…If so, then the detection of OA will be much easier and more accurate. In fact, there have been several studies of blood biomarkers for OA (Ramos et al, 2014; Feng et al, 2015; Ahmed et al, 2016; Bay-Jensen et al, 2018; Costa-Cavalcanti et al, 2018). For example, Ramos et al demonstrated that the mRNA expression of apoptotic pathways was significantly different in the blood of patients with OA (Ramos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation